AKSI AKTIVITAS HADRAH MENCEGAH HIPERTENSI DI KECAMATAN CEMPAKA PROVINSI KALIMANTAN SELATAN - Ilmi, Bahrul; Firdaus, Syamsul; Suroto; Rizani, Akhmad; Fauziah, Erna (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Hypertension is a non-communicable disease, if not controlled it can trigger degenerative diseases such as congestive heart failure, kidney failure and vascular disease and can cause fatal strokes. Based on data from the Banjarbaru City Health Service, in 2018 hypertension was ranked first among the 10 biggest diseases in Banjarbaru City with a total of 3,326. Cempaka Community Health Center had the highest ranking for hypertension among people aged ≥ 45 years with a total of 1,488 people, geographical considerations and ease of guidance were chosen in Cempaka sub-district. The aim of implementing community service is to prevent an increase in hypertension cases in South Kalimantan at the Cempaka Banjarbaru Community Health Center with the mission of increasing community independence in living a clean and healthy lifestyle. The implementation of hadrah exercises for the elderly in the form of physical movements is identical to the implementation of exercise by the elderly and will have an impact on smooth blood flow. Community service results The results of the activities showed an increase in participants' knowledge, during the health education participants were enthusiastic and actively asked questions. There are efforts to change attitudes by forming groups of hadrah exercises which are taught for 30 minutes and they want to carry out these hadrah exercises every day at least 5 times a week. Keyword : Elderly, Hypertension, Hadrah Gymnastics, Health Education.